A mighty oak in the rapidly expanding field of checkpoint inhibition for NSCLC - Christopoulos, Petros; Thomas, Michael (Journal of thoracic disease, 2017)
In the Lancet issue of last December Rittmeyer and colleagues reported the primary efficacy analysis of another landmark immunotherapy study (1): the randomized phase 3 OAK trial comparing atezolizumab (n=425), an anti-programmed death-ligand 1 (PD-L1) monoclonal antibody, with docetaxel (n=425) for patients with squamous or adenocarcinomatous non-small cell lung cancer (NSCLC) progressing after one or more platinum-based combination regimens.
Gesehen am 20.07.2018